Consumer food security and labeling intervention on food products through public policies in Romania - Dacinia Crina Petrescu; Ruxandra Mălina Petrescu-Mag; Florina Bran; Carmen Valentina Rădulescu (Amfiteatru Economic Journal, 2018)
The correct understanding of consumers' food labeling knowledge and perceptions is a prerequisite to develop and implement coherent and appropriate food safety policies. One objective of the paper was to discover how often consumers access and use specific food label information. Another objective was to explore stakeholders' preferences for several public policy options relevant for food safety. In this respect, a survey on a sample of 312 Romanian consumers and the evaluation of several public policy options by four stakeholder groups (food producers and sellers, doctors, fitness trainers, and consumers) were carried out. The results revealed that the most frequently read types of information on the label were "expiration date" and "price", closely followed by "quantity" and "brand". Among tested public policies, those related to the traffic light labels and to the social interest messages with health claims were rewarded with high scores by investigated stakeholders. Although nutrition has a decisive impact on health state, nutrition information was not frequently read by people, thus justifying the implementation of a public policy meant to enhance consumers' interest in and reading frequency of nutrition information on food label.
Keywords: D18; M31; Q18; R28; 330; label; food safety; consumer; label reading behavior; public policy; Romania